De-risking livestock systems through bundled index insurance: why it is important to promote market development for productivity-enhancing inputs - Ochenje, Ibrahim; Shikuku, Kelvin Mashisia; Banerjee, Rupsha R. (International Livestock Research Institute, 2025)
Livestock keepers in East Africa grapple with multiple compounding and cascading risks including extreme weather events, pests and diseases, price fluctuations, and conflict. While several risk management solutions have been implemented mostly as standalone interventions, it is increasingly clear that bundling financial and sociotechnical innovations will be crucial for transforming agri-food systems to address the multiple risks simultaneously, enhance resilience, and improve livelihoods. This brief explains the role of private sector service providers of productivity-enhancing inputs in the diffusion and scaling of bundled index-based livestock insurance crucial for de-risking livestock systems and livelihoods.